A new species of the giant pill-millipede genus Sphaerobelum Verhoeff, 1924 from northern Thailand, with an extensive description and molecular characters (Diplopoda: Sphaerotheriida: Zephroniidae) - Wongthamwanich, Nattarin; Panha, Somsak; Sierwald, Petra; Wesener, Thomas; Thirakhupt, Kumthorn (Zootaxa, 2012)
As a first step towards an inventory of the giant pill-millipedes in Thailand, a new species of the genus SphaerobelumVerhoeff, 1924, S. truncatum n. sp. is described from Nan Province, northern Thailand. A determination key is presentedfor all five known Sphaerobelum species. Clear morphological differences between S. truncatum n. sp. and the other fourSphaerobelum species were found on the anterior telopods. For the first time in Sphaerobelum, the partial mitochondrialCOI gene was sequenced for S. truncatum n. sp. and compared with distance, maximum parsimony and maximum likeli-hood methods to those of species from other giant pill-millipede genera. Sphaerobelum truncatum n. sp. was found to dif-fer from all other analyzed giant pill-millipedes, including species of Zephronia Gray, 1832, by 22–30%, includingnumerous amino acid changes, supporting the separate status of Sphaerobelum among other giant pill-millipede genera.Maximum likelihood and parsimony analyses support the placement of Sphaerobelum in the Zephroniidae. Figures of allrelevant structures of Sphaerobelum truncatum n. sp. are provided to allow the use of these characters in future descriptions of species of the family Zephroniidae.